Posttraumatic stress disorder increases risk of criminal recidivism among justice-involved persons with mental disorders - Sadeh, Naomi (Criminal justice and behavior, 2015)
Posttraumatic stress disorder (PTSD) is a potentially important, yet understudied, mental disorder to consider in models of criminal recidivism. The present study sought to address this gap in the literature with a large-scale secondary analysis of observational data from a sample of justice-involved persons with mental disorders. Administrative data were reviewed for 771 adult jail detainees with mental disorders. Hierarchical logistic regression models showed that PTSD was associated with a greater likelihood of general (arrest for any new charge) and serious (arrest for a new felony charge) recidivism during the year following the index arrest, after controlling for risk conferred by a recent history of arrest, demographic characteristics, and other mental disorders. Furthermore, risk of rearrest for new charges was comparable for PTSD and substance use disorders. Findings show that PTSD increases risk of both general and serious recidivism and suggest it should be considered in interventions to reduce justice-system involvement.